Pewartaan Injil di Era Digital: Analisis Konten Akun Tiktok @thetolerancesquad - Yohanes Yudit (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
Development of digital technology has greatly influenced our lives, including the Church. In facing it, the Church keeps trying to listen to the echo of her mission in the world. Whatever dan whenever, The Curch has always been an ‘agent of salvation’ for the nations. Her presence must always be interpreted in the light of that mission.Thus, the Church couldn’t stand idly by, especially by consciously closing her eyes when hoax, flexing, FoMO, Doomscrolling, and Brain rot were happenned dan spread in the media. The Church needs to involved and actively fight for the values of truth and salvation. The digital era should be a new meeting ground in which the Church can grow and spread the news of salvation for more and more people. This study aims to find the new ways that Church can do in its preaching efforts, especially in this new era. By analyzing the effectiveness of content specifically on the TikTok account @mainmain_official, the presence of the Church is still very relevant to this era. The Church even has great opportunities in its missionary efforts by utilizing technology. This study uses two methods, namely the library method and content analysis. With this method, it was found that the Church can be present in this digital era to proclaim the Gospel and its righteousness, namely by utilizing digital platforms, especially TikTok. The efforts that can be made to increase the success of preaching are by creating creative, interesting, and inspiring content. One form is by displaying daily life testimonies that are relevant to the lives of many people.